2021
DOI: 10.3390/biom11111631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Jasmonate Doped Nanoparticles on Nitrogen Composition of Monastrell Grapes and Wines

Abstract: Nitrogen composition on grapevines has a direct effect on the quality of wines since it contributes to develop certain volatile compounds and assists in the correct kinetics of alcoholic fermentation. Several strategies can be used to ensure nitrogen content in grapes and one of them could be the use of elicitors such as methyl jasmonate. The use of this elicitor has been proven to be efficient in the production of secondary metabolites which increases the quality of wines, but its use also has some drawbacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…On the other hand, in a recent study, Gil-Muñoz et al (2021) showed how MeJ increased the total amino acid content in Monastrell musts although these differences were more noticeable in 2019 compared to 2020; however, Pérez-Álvarez et al (2022), in the same grape variety and seasons, observed that foliar treatments with MeJ supported in nanoparticles had little impact on grape amino acids concentration. Different studies reported that methyl jasmonate, the methyl ester of jasmonic acid (JA), may activate the phenylalanine ammonia-lyase (PAL), which is the key enzyme that catalyses the first step in the phenolic biosynthesis (Belhadj et al, 2006), increasing phenolic composition in grapevines (Portu et al, 2016).…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, in a recent study, Gil-Muñoz et al (2021) showed how MeJ increased the total amino acid content in Monastrell musts although these differences were more noticeable in 2019 compared to 2020; however, Pérez-Álvarez et al (2022), in the same grape variety and seasons, observed that foliar treatments with MeJ supported in nanoparticles had little impact on grape amino acids concentration. Different studies reported that methyl jasmonate, the methyl ester of jasmonic acid (JA), may activate the phenylalanine ammonia-lyase (PAL), which is the key enzyme that catalyses the first step in the phenolic biosynthesis (Belhadj et al, 2006), increasing phenolic composition in grapevines (Portu et al, 2016).…”
Section: Resultsmentioning
confidence: 86%
“…Vine spacing was 2.80 m x 1.25 m. Foliar applications of MeJ and ACP-MeJ were studied. To carry out the treatments, aqueous solutions were prepared with a concentration of 10 mM of MeJ according to Garde-Cerdán et al (2016) and Garde-Cerdán et al (2018), and 1 mM of ACP-MeJ according to Gil-Muñoz et al (2021) and Pérez-Álvarez et al (2022), using Tween 80 as a wetting agent (1 mL/L). The control plants were sprayed only with a water solution of Tween 80.…”
Section: Vineyard Site Grapevine Treatments and Grape Samplesmentioning
confidence: 99%
“…The use of nanotechnology, due to slow release, has been shown to improve the efficiency of MeJ in grapes. A study on Monastrell grapes and wines showed an increase in amino acid composition in foliar treatments with MeJ and nano-methyl jasmonate (nano-MeJ) in a similar way [ 22 ]. In addition, other researchers showed an increase in stilbene content in Monastrell wines from grapes treated with MeJ and nano-MeJ [ 23 ].…”
Section: Introductionmentioning
confidence: 99%